Experimental Study on Thermo-physical Properties of Nano-fluids based on Copper Nanoparticles. (2019) - Kumar Yadav, Shravan; Vasu, V.; Kumar Paliwal, Uday
Abstract: Copper nanoparticles are used in different types of base fluids (vegetable oil, paraffin heavy liquid and engine oil) to prepare Nano fluids and compare the results. Nano fluids are prepared by using Ultrasonicator probe. Thermal conductivity is measured by KD-2 pro and rheological properties are measured by Rheometer. Many efforts allocated to improve heat transfer performance of Nano fluids applied as a coolant. There is a real need to have a multi-lateral consideration about effects of adding nanoparticles to the base fluids. Although the aim of nanoparticles addition is raising the thermal properties, it is essential to see other effects of this addition on base fluids. Thus, other properties of Nano fluids should be considered besides thermal properties, e.g. viscosity, stability, etc. This is a matter of cost to disperse nanoparticles in base fluids to increase the heat removal and dissipation capability of fluids. Therefore, in this paper, relative thermal conductivity and relative viscosity has been investigated and also the effects of particle concentration and temperature on viscosity have studied. On the basis of integrated study of thermal conductivity and viscosity for effective heat transfer, vegetable oil based Nano fluid out performed as compared to paraffin liquid heavy and SAE-20W40.